Outcomes following use of a standard antibiotic protocol in the management of maxillofacial trauma patients - Amit Sethi; Emily Van Huekelom; Pushkar Mehra (Elsevier, 2020)
Purpose: To evaluate the effectiveness of a standard antibiotic regimen protocol in the management of maxillofacial trauma patients. Materials and methods: The study sample included patients with at least one facial fracture and managed by either closed (CR/MMF) or open reduction (ORIF) by the Oral and Maxillofacial Surgery service. A standardized antibiotic administration protocol based on type of treatment performed and timing of surgical intervention was used in the management of all patients. The primary predictor variable was antibiotic usage. The primary outcome measured was postoperative surgical site infection. Bivariate analysis was performed to assess the association between antibiotic exposure and postoperative surgical site infection. A p value of less than or equal to .05 was deemed to be significant. Results: The study sample comprised of 392 patients (102 midface and 290 mandible fractures). The mean age of the study group was 35 years and 89% of the patients were male. Postoperative infection was encountered in 18 patients (all with compound mandible fractures). The infection rates were 3.6% after CR/MMF and 8.7% after ORIF. No patient with midface fractures developed an infection. Chi-square test showed no statistically significant difference in postoperative infection rate in mandible fractures treated either by CR/MMF (p = 0.91) or ORIF (p = 0.94). Conclusions: Use of this antibiotic administration protocol limits antibiotic usage and standardizes their administration in the management of maxillofacial trauma without increasing the rate of postoperative surgical site infections.